2010
DOI: 10.4067/s0717-97072010000300025
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography Coupled With Mass Spectrometry Detection for the Volatile Profiling of Vitis Vinifera Cv. Carménère Wines

Abstract: The volatile metabolome of Vitis vinifera C.V. Carménère wines, a unique Chilean winegrape variety, was characterized in this work. After solvent extraction with dichloromethane (LLE) or head space solid phase microextraction (HS-SPME), the resulting volatile compounds were analyzed by gas chromatographymass spectrometry (GC-MS). Specific methods were carried out too for the determination of methoxypyrazines and thiols. Almost 150 compounds corresponding to aliphatic and aromatic alcohols, organic acids, aceta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…The analysis of volatile compounds by coupled MS techniques, such as GC−MS, has been useful for the volatile metabolome of wines for the purposes of characterization [50]. However, GC-MS also proved suitable for the untargeted approach in which pre-processing and data treatment play a key role.…”
Section: Ms Approachesmentioning
confidence: 99%
“…The analysis of volatile compounds by coupled MS techniques, such as GC−MS, has been useful for the volatile metabolome of wines for the purposes of characterization [50]. However, GC-MS also proved suitable for the untargeted approach in which pre-processing and data treatment play a key role.…”
Section: Ms Approachesmentioning
confidence: 99%
“…Climatic conditions, rather than maturity or terroir, also had a critical effect upon IBMP concentration in grapes . On the other hand, almost 150 volatile compounds were identified in Carmenère wines, corresponding to aliphatic and aromatic alcohols, organic acids, acetate and ethyl esters, lactones, terpenes, norisoprenoids, pyrazines, thiols and phenolic compounds . These authors reported that 3‐mercaptohexyl acetate (3MHA), 3 mercaptohexan‐1‐ol (3MH), benzenemethanethiol (BM), 2‐furanmethanethiol (2FM) and IBMP showed significant odorant properties.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
“…These authors reported that 3‐mercaptohexyl acetate (3MHA), 3 mercaptohexan‐1‐ol (3MH), benzenemethanethiol (BM), 2‐furanmethanethiol (2FM) and IBMP showed significant odorant properties. On the other hand, 2‐isopropyl‐3 methoxypyrazine (IPMP) and 4‐mercapto‐4 methylpentan‐2‐one (4MMP) were not detected . β ‐Damascenone, several thiols, ethyl octanoate, 2‐phenylethanol, and 2‐isobutyl‐3‐methoxypyrazine showed significant odor activity values (OAV) and were correlated with different attributes such as cooked fruits, berry‐like and herbaceous notes, characteristic of Carmenère wines .…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Domínguez and Agosin (2010) identified 150 volatile compounds in wine using both solvent extraction with dichloromethane and HS-SPME which appeared to be complementary. In another study, Domínguez and Agosin (2010) identified 150 volatile compounds in wine using both solvent extraction with dichloromethane and HS-SPME which appeared to be complementary.…”
Section: Lloyd Et Al Application Of Metabolomics To Wine Science 727mentioning
confidence: 99%